Introducing Offlineness: Theorizing (Digital) Literacy Engagements. (March 2020) - Nelson, Elizabeth L.; Perry, Mia; Rogers, Theresa
In this Insights essay, we propose a new concept of offlineness that builds on current language around digital practices, yet addresses an element of young people's experience that is not adequately represented in current research or educational discourse. This work is informed by a recent cross-national arts-based research project that highlighted the limitations of the discourse ascribed to the nature of young people's engagement with digital literacies. We propose a (re)theorization, which builds on a critical review of current conceptual research and digital commentaries. Theorizing offlineness as a continuum between online and offline practices is tantamount to a paradigm shift toward more nuanced understandings of young people's digital practices. It offers researchers and educators a more precise way to speak to young people's digital experiences, providing a productive tool to (re)construct learning and inquiry spaces in literacy research and education.